The Effect of Communication and Physical Work Environment on Employee Performance at PT.Vadhana International Palembang Branch - Ririn Agustina (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to analyze the effect of communication and physical work environment on the performance of employees of PT Vadhana International Palembang Branch. This research used primary data and secondary data through distributing questionnaires to all 72 respondents. The research method used is multiple linear regression analysis. The resultsindicate that communication (X1) and physical work environment (X2) had a significant effect on employee performance (Y). This research is useful for improving employee performance through communication and the company's physical work environment.